2015
DOI: 10.1016/j.ijcha.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the severity and extent of coronary artery disease

Abstract: ObjectiveTo investigate whether women presenting with suspected angina would show less severe coronary artery disease in than men as determined by the extent score.MethodsWe examined 994 participants of the Australian Heart Eye Study presenting for coronary angiography in the investigation of chest pain from June 2009 to February 2012. People were excluded if there was a history of coronary artery bypass surgery, previous stenting procedure or incomplete angiogram scoring. An extent and vessel score was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
15
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 30 publications
10
15
2
Order By: Relevance
“…In this study the IHD was found to be more prevalent in males 63% than their female counterparts which is similar to the findings reported in other studies that males are more prone to IHD than females (Beltrame et al, 2009;Bhopal et al, 1999;Chiha et al, 2015;Kinra et al, 2010;Ngian et al, 2012;Yahagi et al, 2015). Test of proportion showed that most of the patients 73% were significantly higher in the age group 61-80 years.…”
Section: Discussionsupporting
confidence: 92%
“…In this study the IHD was found to be more prevalent in males 63% than their female counterparts which is similar to the findings reported in other studies that males are more prone to IHD than females (Beltrame et al, 2009;Bhopal et al, 1999;Chiha et al, 2015;Kinra et al, 2010;Ngian et al, 2012;Yahagi et al, 2015). Test of proportion showed that most of the patients 73% were significantly higher in the age group 61-80 years.…”
Section: Discussionsupporting
confidence: 92%
“…The similar result from Chiha J, et al, said that women had less severe CAD than men significantly, but not in MI patients. (18) Our hypothesis had been proven in present study that abnormal ABI was an independent risk factor for multivessel CAD and it was associated with more prevalent multivessel CAD in ACS patients (OR 4.83; p=0.021).…”
Section: Referencessupporting
confidence: 58%
“…We used lower ABI (more patients would be identified), because it has better sensitivity and it was a good predictor for PAD. (17) Sex (male) had been established in another study to be associated with the presence of multivessel CAD (18), but in our study its statistically significances showed only with another variable in binary logistic regression. This might be Table 3.…”
Section: Methodscontrasting
confidence: 51%
“…The literature has consistently shown women are more likely to present at an advanced stage of disease with greater severity of symptoms than their male counterparts and with a greater comorbidity burden at the time of surgery (12). The pattern of distribution of coronary artery disease can exhibit marked sex differences with certain higher grade disease patterns seen in women (13).…”
Section: Discussionmentioning
confidence: 99%